2015
DOI: 10.1016/j.jhep.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of functional variants in IFNL4 and IFNL3 for association with HCV clearance

Abstract: Background & Aims Genetic polymorphisms within the interferon lambda (IFN-λ) region are strongly associated with hepatitis C virus (HCV) clearance; the IFNL4-ΔG/TT (rs368234815) polymorphism, which controls generation of the IFN-λ4 protein, is more strongly associated with HCV clearance than rs12979860 (the ‘IL28B variant’). An IFNL3 3′ untranslated region polymorphism (rs4803217) has been proposed as a causal variant that may affect HCV clearance by altering IFNL3 mRNA stability. Methods We compared IFNL4-Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 43 publications
5
76
0
Order By: Relevance
“…First, the mechanism by which the IFNL3 rs12979860 SNP exerts an effect on ISG signaling in any cell type is unsettled, with uncertainty about whether the SNP is actually functional or whether its effect is mediated by other IFNL SNPs in high linkage disequilibrium (33). Individuals with a ΔG genotype (vs. T) at the IFNL4 variant rs368234815 express a transcript encoding the IFN-λ4 protein, which has been demonstrated to induce IFN signaling (33,34). All of the NPC subjects and mothers from our study were genotyped at rs368234815, and in each individual there was a direct correlation between IFNL3 SNP rs12979860 and IFNL4 rs368234815 genotypes (Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the mechanism by which the IFNL3 rs12979860 SNP exerts an effect on ISG signaling in any cell type is unsettled, with uncertainty about whether the SNP is actually functional or whether its effect is mediated by other IFNL SNPs in high linkage disequilibrium (33). Individuals with a ΔG genotype (vs. T) at the IFNL4 variant rs368234815 express a transcript encoding the IFN-λ4 protein, which has been demonstrated to induce IFN signaling (33,34). All of the NPC subjects and mothers from our study were genotyped at rs368234815, and in each individual there was a direct correlation between IFNL3 SNP rs12979860 and IFNL4 rs368234815 genotypes (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes of NPC and postpartum subjects at IFNL3 SNP rs12979860 and IFNL4 were determined as described (18,34). Briefly, genomic DNA was isolated from patient samples by using the PureLink Genomic DNA Mini Kit (Qiagen) per the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The rs12979860 SNP itself may not be functional; rather, its effect appears to be mediated by other closely linked IFN-λ polymorphisms, including the IFNL4 ΔG/TT variant rs368234815 (26,27). The ΔG frameshift variant permits production of the novel protein IFN-λ4, which is paradoxically associated with impaired resolution of HCV infection (26,27). In our cohort, the favorable IFNL3 rs12979860 C allele was in 100% linkage disequilibrium with the favorable IFNL4 rs368234815 TT allele (Table S1).…”
Section: Resultsmentioning
confidence: 90%
“…The mechanism by which polymorphisms at rs12979860 might contribute to control of HCV after pregnancy is not clear. The rs12979860 SNP itself may not be functional; rather, its effect appears to be mediated by other closely linked IFN-λ polymorphisms, including the IFNL4 ΔG/TT variant rs368234815 (26,27). The ΔG frameshift variant permits production of the novel protein IFN-λ4, which is paradoxically associated with impaired resolution of HCV infection (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…A recent report compared the strength of association of rs4803217 and rs368234815 in IFN treatment response in HCV-infected African Americans, who have the lowest reported LD values among all ethnicities between rs368234815 and rs12979860 SNPs (Figure 1b). 107 They found that rs368234815 was more strongly associated with the outcome than rs4803217. 107 In another independent report, Lu et al applied multivariate regression to test the independence of rs368234815 from rs4803217 in predicting response to IFN treatment in HCV patients of AfricanAmerican decent.…”
Section: Transcription Studies On the Ifnl4 Genementioning
confidence: 99%